Efficient synthesis of a 6-deoxy-talose containing tetrasccharide found in Franconibacter helveticus LMG23732T. (2nd May 2018) - Xu, Yiren; Xu, Tianheng; Zhang, Jianjun
Abstract: Synthesis of the 6-deoxy-talose (6-dTal) containing tetrasaccharide, naturally found in Franconibacter helveticus LMG23732T, has been described. The synthetic method utilized an allyloxyethylidene group for protecting the 1-OH and 2-OH groups of rhamnopyranose and a redox reaction for synthesizing 6-deoxy talose, which eventually formed a disaccharide containing α-Glc p -(1→2)-6dTal p configured glycosidic bonds using a [2 + 2] synthetic strategy. Graphical abstract: Highlights: We have reported a convergent total synthesis of a tetrasccharide analogue. Stereo- and regio-specific synthesis was achieved in Schmidt glycosylation employing protected L-talopyranosyl and D-glucopyranosyl building blocks. The synthesis involves an allyloxyethylidene group and a redox reaction of rhamnopyranoside derivative for the synthesis of 6-deoxy talopyranoside.